2022
DOI: 10.1108/qae-01-2022-0008
|View full text |Cite
|
Sign up to set email alerts
|

A look at student performance during the COVID-19 pandemic

Abstract: Purpose This study aims to use self-reported publicly available student assessment data from the time period when there was an abrupt change in instructional method at the start of COVID-19 to assess potential for differences as a result of course delivery mode. Design/methodology/approach A general linear model using 837 student evaluations from 191 US public higher education institutions investigates the impact on student performance and how performance was related to a number of covariates, namely, online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 31 publications
2
25
0
1
Order By: Relevance
“…This statement is further supported by Broadbent (2017), wherein students saw an improvement in their final grades following the implementation of an online learning setup. Moreover, the same case occurred in the United States wherein students' GPA improved by 0.10 during the pandemic (Cavanaugh et al, 2022). The same results were also seen in China: students' mean average grades improved during the pandemic (Zhao et al, 2022).…”
Section: Positive Effects Of Online Learning Strategy On Students' Pe...supporting
confidence: 58%
See 1 more Smart Citation
“…This statement is further supported by Broadbent (2017), wherein students saw an improvement in their final grades following the implementation of an online learning setup. Moreover, the same case occurred in the United States wherein students' GPA improved by 0.10 during the pandemic (Cavanaugh et al, 2022). The same results were also seen in China: students' mean average grades improved during the pandemic (Zhao et al, 2022).…”
Section: Positive Effects Of Online Learning Strategy On Students' Pe...supporting
confidence: 58%
“…His findings illustrate the positive impacts of virtual learning on the academic performance of students in aspects like increased self-directed learning, improved attitudes, improved motivation, and better academic results. Another found that student performance during the pandemic varied by course level and instructional mode, with some students experiencing academic loss and others experiencing academic gain (Cavanaugh et al, 2022). Afghan students' academic performance and satisfaction with online teaching were found to be negatively impacted by the pandemic (Hashemi, 2021).…”
Section: Positive Effects Of Online Learning Strategy On Students' Pe...mentioning
confidence: 99%
“…Online teaching methods have been shown to work well for content that is usually delivered in lectures or classroom sessions. One US study, which included 837 student evaluations from 191 public higher education institutions, found that the rapid transition to online instruction in 2020 did not negatively impact student performance and may have marginally increased these marks ( 29 ). It is worth noting, however, that no health professional degrees were included in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Others who preferred the face-to-face teaching delivery process may get bored easily in learning and struggled to work consistently (Limniou, 2021 ). Cavanaugh et al investigated the impact on student performance during pandemics from 191 public higher education institutions in USA, and they found that the overall grade point average was even increased by 0.10 (out of 4.0), and they believed that the student grades as a whole did not suffer from the difficulties of learning during pandemics (Cavanaugh, 2023 ).…”
Section: Related Workmentioning
confidence: 99%